2015
DOI: 10.1508/cytologia.80.317
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological and Molecular Characterization of F<sub>1</sub> Hybrids between <i>Brassica tournefortii</i> and <i>B. rapa</i>

Abstract: Summary Interspecific F 1 hybrids were synthesized between Brassica tournefortii (2n=20, TT) and B. rapa var. yellow sarson (NRCYS-05-02) (2n= 20, AA) by sexual mating. The F 1 s were obtained only when B. tournefortii was used as the female parent. Morphological, cytological and sequence tagged microsatellite sites (STMS) based molecular analyses were carried out to confirm the hybrid nature of F 1 plants. Morphologically, the F 1 plants were intermediate for most of the morphological attributes. Although, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This can be achieved through effective utilization of germplasm resources by integration of genomic tools to impart efficiency and pace to breeding processes (Banga 2012). The insufficient intra-specific variability can be addressed using untapped genetic diversity in relative species (Kumar et al 2015).…”
mentioning
confidence: 99%
“…This can be achieved through effective utilization of germplasm resources by integration of genomic tools to impart efficiency and pace to breeding processes (Banga 2012). The insufficient intra-specific variability can be addressed using untapped genetic diversity in relative species (Kumar et al 2015).…”
mentioning
confidence: 99%
“…Cytological analysis of F 1 hybrids (2n=34) not only confirmed their hybridity but also indicated the extent of genome homoeology between the parents. Meiotic analysis of F 1 hybrids showed the predominance of univalents that ranged between 4-22 to 6-24, which is the typical feature of wide hybrids (Kumar et al 2013(Kumar et al , 2015b. It was observed that PMCs had chromosome association on an average of 0.70 IV +0.72 III +6.60 II +12.80 I , 0.76 IV +0.84 III +7.92 II +13.76 I and 0.68 IV +0.36 III + 7.54 II +10.55 I , respectively in F 1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the sustainable production of any crop, improved and well-adapted varieties should be continuously released. For this purpose, a good genetic variability should be present in the primary gene pool (Shinwari et al, 2013;Shinwari et al, 2014;Kumar et al, 2015;Jan et al, 2017 a, b ). Since there is a limited genetic variability in rapeseed germplasm, various tools should be employed to broaden such variability (Sestili et al, 2010;Khan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%